Чеський паремійний фонд: культурно-історичні джерела формування і тенденції розвитку - Даниленко, Л.І. (Мовознавство, 2013)
Статтю присвячено аналізу античних і біблійних джерел чеського паремійного фонду. За формою освоєння античної спадщини виділено три типи паремійних висловів, які ґрунтуються на принципі мотивування їх внутрішньої форми. Коротко схарактеризовано переклади Біблії чеською мовою. Основна увага зосереджена на біблійних джерелах, з яких походять чеські паремії, та на семантиці цих одиниць. Наводяться відповідники українською мовою. Для виявлення тенденцій розвитку сучасної чеської пареміології в Чехії проведено соціолінгвістичний експеримент методом анкетування та визначено паремійний мінімум. Article researches ancient and Bible sources of Czech paremia fund. Based on the form of ancient
heritage three types of paremia sayings are described, that depend on the principle of motivation
of their inner form. Paremia of the first type have the same invariant of meaning and the same inner
form. Paremia of the second type have the same invariant of meaning, but similar by semantics
inner form. Paremia of the third type differ from ancient by peculiarities of metaphoric meanings and
by structure.
Special attention is paid to Latin proverb Tunica propior pallio est, which is known in Czech
language as ВШиьн ko/ьііе neh kab6t and in Ukrainian Своя сорочка do тіла ближча.
In XVII-XVIII the structure of Czech proverb included different lexical composition. Article
suggests historic and etymological reconstruction of semantics of the above mentioned paremia unit
in connection with the meaning of the words sukno, sukne, ко/ьііе.
Bible translations into Czech language are characterized in brief. The main area of research
includes Bible sources, from which Czech paremia originated. Their semantics is analyzed including
corresponding Ukrainian units.
In order to reveal the trends of development of modem Czech paremiology author visited Czech
Republic to conduct socio-lingual experiment using surveys to find out paremia minimum. Author
conducted comparative analysis of our research and research of Czech authors D.Bittnerova and
F.Shindler. The conclusion is that despite the difference in quantity of paremia units analyzed, the result
was almost the same: half of proverbs and sayings known by more than 95 % informants is
exactly the same in both researches. However, «proverb knowing» and «proverb using» is not the
same thing. Survey indicated that the youth rarely uses proverbs in everyday communication.
The issue if new proverbs and sayings do spring up in modem language and what criteria we should
use to reveal them is still to be discussed.